Retrospective Evaluation of Amniocentesis Cases - Ayhan Coşkun; Deniz Cemgil Arıkan; Gürkan Kıran; Melih Atahan Güven; Bülent Köstü; Sedar Ceylaner (Medical Network, 2009)
OBJECTIVE: The aim of this study is to evaluate retrospectively the indications, karyotype results and complications of amniocentesis that we performed in our clinic. STUDY DESIGN: Between January 2005 and May 2008 at the Department of Obstetrics and Gynecology Clinic of Kahramanmaras Sutcu Imam University, 340 amniocentesis procedure were performed. RESULTS: The biggest amniocentesis indication group, with 47% (160 in 340), was high risk at triple test followed by the advanced maternal age with 25% (86 in 340 ). Chromosomal abnormality was found in 15 (4,4%) of 340 cases after the result of karyotype analyses. Chromosomal abnormality was determined in 3 of the 160 patient (1,8%) with high risk at triple test, 3 of the 86 patient (3,5%) with advanced maternal age, 1 of the 29 patient (3,4%) with high risk at double test, 6 of the 41 patient (14,5%) with abnormal ultrasound findings, 2 of the 7 patient (28,6%) with increased NT thickness. Six cases (1,7%) had vaginal bleeding in the week following amniocentesis and 3 of these (0,9%) ended in abortion. CONCLUSION: Although it might lead to serious complications including fetal loss, amniocentesis is the most commonly and easily performed, and reliable invasive test for prenatal diagnosis of genetic disease.